A proposal for a new prescriptive discounting scheme: The intergenerational discount rate - Stéphane Hallgatte (Fondazione Eni Enrico Mattei (FEEM), 2008)
Cost-benefit analyses require comparing costs and benefits that occur at different points in time. Doing so, however, creates conflicts between short-term considerations a discounting scheme has to be consistent with observed behaviours and long-term ethical issues a discounting scheme must not favour the current generation over future ones. To overcome this conflict, the present article proposes a prescriptive consumption discounting scheme that applies different discount rates (i) for various incomes in the lifetime of a unique individual and (ii) for various incomes that affect different individuals. Practically, any income flux is first discounted to the birth date of all individuals using a discount rate with a non-zero pure preference for the present; then these individual discounted values are discounted to the present with a discount rate with no preference for the present and finally summed up. The aim of this prescriptive discount rate is to be consistent with observed individual behaviour (descriptive discount rate) without favouring current generations. Consequences are discussed and compared with the UK Green Book and the Stern Review discounting schemes.
Keywords: H4; 330; Discount Rate; Intergenerational Equity; Klimaschutz; Abzinsung; Overlapping Generations; Theorie